BOTÁNICAS UNPLUGGED: LATINOS’ RELIGIOUS HEALING AND THE IMPACT OF THE IMMIGRANT CONTINUUM - Viladrich, Anahí (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Botánicas (literally botanies) are local dispensaries that offer spiritual, healing, and religious services to a mostly Latino and Caribbean population in the United States (U.S). Despite the vast literature on Latinos’ alternative medical systems, little is known on the role of the informal economy of healing in the urban milieu. This paper attempts to fill this vacuum by addressing the role of botánicas in meeting the religious healing and mental health needs of the growing Latino population in New York City (NYC).Materials and Methods: A two-stage ethnographic study on botánicas took place between 2004 and 2016 in NYC. During the first stage (2004–2006), a research team conducted participant observation and ethnographic mapping. This entailed the identification of two major concentrations of botánicas in Queens and the Bronx, with smaller clusters found in Manhattan and Brooklyn. Participant observation and in-depth interviews were conducted with fifty-six healers during this phase of the project, and thirty in-depth interviews were accomplished during the second phase (2014–2016), which focused on the products and services offered by botánicas in Queens. Results: Botánica providers and spiritual counselors construct a language of illness — supported by the sociosoma model — that calls attention to the contextual factors of distress, including the harmful effect of troubled relationships in Latinos’ lives. Most providers identified the “immigrant continuum” as one of the main causes of their patients’ suffering. In this vein, they highlighted the impact of Latinos’ undocumented status, family conflicts and financial concerns as key triggers of their deleterious mental health conditions. Participants also shared a holistic explanatory model of mental illness, which combines social stressors and divine causas (causes) as the main source of Latinos’ mental and emotional suffering. Two main ailments, depression and nervios (nervousness) were seen as complementary and closely related to the multifarious impact of the immigrant continuum in Latinos’ lives. These conditions were treated with natural medicines (e.g., herbs), informal counseling and religious ceremonies, such as prayer and ritual cleansing. Conclusion: The paper sheds light on the role of botánicas, and their providers, in supporting a shared language of illness among Latinos in the U.S. The prevalence of two mental ailments among Latinos, depression and nervios, informs culturally-based processes of diagnosis and treatment in an urban multiethnic milieu. The article ultimately highlights the need for additional theoretical models and empirical research focused on Latinos’ growing mental-health issues in the U.S.